STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN BRAND AWARENESS PRODUK HANDPHONE MERK SAMSUNG DI TOKO GMT BAUBAU - Pratiwi, Indah Eka (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
The purpose of this study was to determine the marketing communication strategy of GMT Baubau store in increasing brand awareness of Samsung brand cellphone products. This research uses a qualitative method with a case study approach. The data collection techniques used were observation, in-depth interviews, and documentation studies. The data analysis technique used in this research is qualitative descriptive analysis technique. The results of this study show that the GMT Baubau store has successfully implemented a holistic and measurable marketing communication strategy to increase brand awareness of Samsung brand mobile products. The focus of marketing is on social media, especially Instagram and Facebook, as well as organizing sales promotions, such as cheap redemption/gift every year, creating active interaction with consumers and providing attractive offers. Although faced with barriers such as price competition, promoters, and similar products with high specifications, GMT Baubau stores need to continue to create added value, build positive shopping experiences, and improve interactions with consumers. A more competitive pricing strategy and a conventional marketing approach through brochures can also be differentiation factors. Thus, the GMT Baubau store can overcome challenges in a fierce competitive environment and strengthen brand awareness of Samsung brand mobile products, making the GMT Baubau store the main destination for consumers in finding quality products with attractive added value.